2021
DOI: 10.1088/1742-6596/1818/1/012128
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Corrosive Substance as Green Inhibitor for Carbon Steel in Saline and Acidic Media

Abstract: Ficus (FIC) leaf extract used as corrosion inhibitor for carbon steel alloy (C.S) in two corrosive environments (saline and acidic) with four concentrations (1, 2, 3 and 4 ppm) at varied temperature range between (298-328 K) using electrochemical polarization measurements. The importance of this work focused on the use the green chemistry that is far from the chemical materials effect. The results of polarization presented the FIC inhibitor consider a mixed type (anodic and cathodic) inhibitor. Tafel curve use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The result of progesterone hormone of recent study revealed nonsignificant variation P> 0.05 between the study group in pregnant infected women, also [26] found no significant difference in progesterone levels among infected pregnant women. These results agreed with [28,29].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The result of progesterone hormone of recent study revealed nonsignificant variation P> 0.05 between the study group in pregnant infected women, also [26] found no significant difference in progesterone levels among infected pregnant women. These results agreed with [28,29].…”
Section: Discussionsupporting
confidence: 92%
“…The study was carried out during the period from October 2021 to February 2022 on (200) pregnant women who attended to various governmental hospitals in Maysan province of Iraq with their ages ranged from (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) years. Venous blood samples were collected from all pregnant women enrolled in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, MDA was correlated positively with WHpR (Figure 1) in OH patients which introduce other influencer (overweight) that increases oxidative stress. Overweight increases oxidative stress by enhancing the production of ROS and reducing antioxidants [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in the material of construction, application of protective coatings, cathodic protection, and application of inhibitors to change the corrosive environment have all been used to prevent and control corrosion of oil and gas pipelines [14]. Inhibitors are among the most widely used methods of corrosion treatment and are categorized as inorganic, organic, surfactant, or mixed substance inhibitors.…”
Section: Introductionmentioning
confidence: 99%